2018
DOI: 10.1111/bjd.16367
|View full text |Cite
|
Sign up to set email alerts
|

How should minimally important change scores for the Patient-Oriented Eczema Measure be interpreted? A validation using varied methods

Abstract: SummaryBackgroundThe Patient‐Oriented Eczema Measure (POEM), scored 0–28, is the core outcome instrument recommended for measuring patient‐reported atopic eczema symptoms in clinical trials. To date, two published studies have broadly concurred that the minimally important change (MIC) of the POEM is three points. Further assessment of the MIC of POEM in different populations, and using a variety of methods, will improve interpretability of the POEM in research and clinical practice.ObjectivesTo calculate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 22 publications
6
42
1
Order By: Relevance
“…These percentage values provide recommendations of how to interpret changes on an improvement in the CADIS and its domain scores (Table ). The suggested interpretation for the CADIS scores is in accordance with a previously published guide on change scores of the Patient‐Oriented Eczema Measure …”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These percentage values provide recommendations of how to interpret changes on an improvement in the CADIS and its domain scores (Table ). The suggested interpretation for the CADIS scores is in accordance with a previously published guide on change scores of the Patient‐Oriented Eczema Measure …”
Section: Discussionsupporting
confidence: 69%
“…If a change in CADIS scores is greater than the SDC, there is a 95% chance that the change in score is real and not just a random variation. Therefore, the MIC of the CADIS should be greater than the SDC to be useful and relevant …”
Section: Methodsmentioning
confidence: 99%
“…A systematic review that included studies looking at the measurement properties of POEM concluded that there was limited evidence for good internal consistency, moderate evidence for good construct validity, good responsiveness and good content validity, and unclear evidence of test–retest reliability and measurement error . Interpretation of POEM has been assessed in the form of the minimally important change and severity bandings . Pearson's correlation coefficients were used to assess the relationship between POEM (measuring patient‐reported symptoms) and the newly developed instrument.…”
Section: Methodsmentioning
confidence: 99%
“…As we have four groups, we powered our sample size calculation to detect a clinically meaningful differences in six pairwise comparisons subsequent to a global test. We estimate that 416 participants (104 in each group) are required to detect a difference of 3.0 in POEM scores12 19 20 between any two groups with 90% power and a significance level of 0.05 (after adjustment for multiple pairwise comparisons). We assumed a SD of 5.5 (SD of 4.89 observed in feasibility trial21 to allow for greater variability in the data or smaller differences to be detected.…”
Section: Methods and Analysismentioning
confidence: 99%